Efeitos da desertificação na composição de espécies do bioma Caatinga, Paraíba/Brasil - Bartolomeu Israel Souza; Rafael Menezes; Rafael Cámara Artigas (Investigaciones Geográficas, 2015)
Desertification is recognized as the land degrada - tion in arid, semiarid, and dry sub-humid zones, as a result from multiple anthropogenic impacts such as unsustainable natural resources management and land-use. In this context, the plant cover displays a crucial role due its capacity of soil protection against both terrestrial runoff and high rates of rain infiltration. In Brazil, the desertification has reached mainly the Seasonally Dry Tropical Forest ( STDF ) biome, natively known as Caatinga, in which the major drivers are related to the historical severe deforestation and livestock expansion. In face of this alarming scenario, there is no or few information about direct effects driven by desertifica - tion, particularly those related to the floristic composition of affected areas or affected potentially areas. Herein, the aim was to assess the desertification effects on vegetation composition within three sites in the Brazilian semiarid zone. In order to ensure unbiased comparisons, the three sampling sites presented similar topographical, pedological and climate conditions, localized at distinctive municipality from Paraíba State, Northeastern region, Brazil. In each site, two contrasting situations were sampled, - desertified and non-desertified environments. These environments were previously selected though satellite images, using the NDVI technique, for identification of vegetation biomass level. In field, the floristic composition was surveyed by transect method, covering a patch of 50m x 4m delimitated with me - tric tape. In these perimeters, it was identified the specie and botanical family of each plant, richness (S) and abundance (N) of tree with DBH ≥ 10 cm. Posteriorly, it was calculated the Shannon’s diversity (H’) and Piellou ́s evenness (J’) by Primer software (open access). Non-parametric univariate (U test) and multivariate (nMDS) analysis were performed to verify differences in the vegetational variables (S, N, H’ and J’) and to demonstrate dissimilarities patterns (relative abundance) for the contrasting environments, respectively. In total, twenty-six plant species were identified, belonging to thirteen families. Of this set, seventeen species (65%) were exclusive of non-desertified areas and only two species were exclusive of desertified areas. U test showed that the both richness and diversity of plants species differed signi - ficantly between the two analyzed environments. Using a subset of 10 species most common in two environments, the nMDS discriminated three groups of plants: i) species asso - ciated to non-desertified areas ( Anadenanthera columbrina, Bauhinia cheilantha and Tabebuia impetiginosa ), ii) species related to desertified areas ( Aspidosperma pyrifolium, Jatropha molissima, Mimosa tenuiflora and Pilosocereus gouneleii ) and iii) species with high density in both environments ( Croton sonderianus, Piptadenia stipulacea e Poincianella pyrami - dalis ). Dominant species in the non-desertified areas are restricted to the environments better preserved of Caatinga, which cannot to support strong degradation condition, whereas the species most common in the desertified areas are recognized as pioneer for the biome. Occurring to the two environments, such species harbors high capacity of settlement to the either impacted or preserved environments coupled to a strong resistance and resilience to disturbance (e.g. log and burn). Finally, the results obtained pointed out that the desertification triggered pervasive changes on the vegetational components (richness and diversity) and floristic composition of the Caatinga biome, suggesting also that human-induced disturbances were determinants to the establishment of the different environments.